Participant Characteristics and Clinical Trial Decision-making Factors in AIDS Malignancy Consortium Treatment Trials for HIV-infected Persons with Cancer (AMC #S006) - Burkhalter, Jack E. (HIV Clin Trials, 2018)
BACKGROUND. Overall, people living with HIV/AIDS (PLWHA) are living longer, but compared with the general population, they are at elevated risk for numerous AIDS-defining and non-AIDS-defining cancers. The AIDS Malignancy Consortium (AMC) is dedicated to conducting clinical trials aimed at prevention and treatment of cancers among PLWHA. OBJECTIVE. To examine patient-level characteristics and perceptions that influence decision-making regarding AMC treatment trial participation. METHODS. PLWHA diagnosed with cancer or anal high-grade intraepithelial neoplasia who were ≥ 18 years old and offered participation on a therapeutic AMC clinical trial were eligible. Participants completed a 17-item survey assessing sociodemographic and other factors potentially influencing decision-making regarding trial participation. RESULTS. The sample of 67 participants was mainly male (n = 62, 92.5%), non-Hispanic (89.5%) and white (67.2%), with a mean age of 48.3 years. About half of participants were screened for lymphoma studies. Nearly all (98.5%) of the participants learned about AMC clinical trials from a medical provider, most (73.1%) knew little about clinical trials in general, and half decided on trial participation on their own. Altruism was the most frequently cited reason for trial participation. Participant recommendations for improving AMC trial accrual included systems changes to speed access to clinical trials and reduce participant burden. CONCLUSIONS. This formative study highlights the perceived benefits to others, i.e., altruism, as an important factor in trial decision-making, little knowledge about clinical trials in general, and the role of physicians in informing participants about clinical trials. Future research should address knowledge barriers and explore systems- and provider-level factors affecting accrual to AMC trials.